Wprowadzenie do zarządzania elektroniczną dokumentacją archiwalną - Wójtowicz Radosław (Introduction to Archival Electronic Documentation Management, 2005)
The article contains the introduction to selected problems concerning archival documentation management. The first part presents basic concepts connected with archiving and the characteristcs of achival contents as resources of economic and social knowledge. The following part presents the premises for improving archival documentation management processes. The last part of the article contains a description of selected information technology tools used in building electronic documentation management systems.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1081, s. 132-140